1986
DOI: 10.1530/jrf.0.0760231
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-induced stimulation of progesterone production by cow luteal cells in vitro

Abstract: The addition of acetylcholine or histamine (10(-7) to 10(-4) M), gamma-aminobutyric acid, a dopamine agonist, and melatonin (10(-7) to 10(-5) M) did not alter basal or LH-stimulated progesterone production (P greater than 0.05). The addition of the specific beta 2-adrenergic agonist terbutaline and salbutamol did not significantly elevate progesterone production. Treatment of luteal cells with serotonin (5-HT), 10(-6) to 10(-4) M, increased the production of progesterone (P less than 0.05). This stimulated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…It is possible that pCPA or NAL acted directly on the ovary. Serotonin can have luteotropic actions directly on luteal cells [52,53], while opioid peptides are present in the ovary [54,55],…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that pCPA or NAL acted directly on the ovary. Serotonin can have luteotropic actions directly on luteal cells [52,53], while opioid peptides are present in the ovary [54,55],…”
Section: Discussionmentioning
confidence: 99%
“…In the rabbit, in-vitro responses to PGF-2a were dependent both on dose and time of incubation (Puri & Laumas, 1975), . In the cow, melatonin did not stimulate progesterone production in short-term incubation of luteal cells (Battista & Condon, 1986) but did stimulate progesterone production by granulosa cells in culture (Webley & Luck, 1986). This was also the case with human cells (Webley & Luck, 1986;Webley et ai, 1988).…”
Section: Discussionmentioning
confidence: 86%
“…Besides the previously described motor effects on the follicle wall (O'Shea & Phillips, 1974;Gimeno et al, 1976;Talbot & Schroeder, 1982), it is suggested that 5-HT stimulates progesterone synthesis in bovine luteal cells in vitro (Battista & Condon, 1986). Also the ovarian concentration of 5-HT has been shown to increase during the oestrous period in cycling rats (Clausell & Soliman, 1978).…”
Section: Recording Of Tritium Releasementioning
confidence: 86%